1997
DOI: 10.1210/jcem.82.11.4378
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic Congenital Hyperthyroidism due to a Spontaneous Germline Mutation in the Thyrotropin Receptor Gene*

Abstract: Neonatal hyperthyroidism in the absence of maternal autoimmune thyroid disease and without thyroid-stimulating antibodies in the child is rare. We here describe a boy with severe intrauterine hyperthyroidism and advanced bone age in the absence of thyroid-stimulating autoantibodies. After long term antithyroid treatment and relapse of hyperthyroidism, a near-total thyroid resection was performed. The necessity to progressively decrease postoperative thyroid hormone replacement indicates thyroid tissue regrowth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 17 publications
5
58
1
Order By: Relevance
“…Based on the previous reports of sporadic congenital nonautoimmune hyperthyroidism [3][4][5][6][7][8][9][10][11] (Table 1), almost all cases were marked by premature delivery and the onset of hyperthyroidism within 1 year. In cases who were poorly controlled with antithyroid therapy, surgery was performed before the age of 10 years [3,[5][6][7][8][9][10]. The most common clinical findings in these patients were marked bone age acceleration, causing abnormality of bone structure in several cases [5][6][7].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Based on the previous reports of sporadic congenital nonautoimmune hyperthyroidism [3][4][5][6][7][8][9][10][11] (Table 1), almost all cases were marked by premature delivery and the onset of hyperthyroidism within 1 year. In cases who were poorly controlled with antithyroid therapy, surgery was performed before the age of 10 years [3,[5][6][7][8][9][10]. The most common clinical findings in these patients were marked bone age acceleration, causing abnormality of bone structure in several cases [5][6][7].…”
Section: Discussionmentioning
confidence: 96%
“…In cases who were poorly controlled with antithyroid therapy, surgery was performed before the age of 10 years [3,[5][6][7][8][9][10]. The most common clinical findings in these patients were marked bone age acceleration, causing abnormality of bone structure in several cases [5][6][7]. When the exophthalamus is detected at the onset of hyperthyroidism, it usually does not progress during the years of follow-up, but resolves after antithyroid drug therapy [4,5,7,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further work is required to determine the true nature of this mutation. Another mutation, Ser-505<Asn, has been detected as a sporadic heterozygous germline mutation in four previous human studies (Schwab et al 1996, Holzapfel et al 1997b, Fuhrer et al 1999, Wonerow et al 2000, and also reported as a somatic heterozygous mutation in human hyperthyroidism (Trulzsch et al 2001).…”
Section: Tablementioning
confidence: 89%
“…The presence of either congenital or adulthood-onset hyperthyroidism, multinodular goiter (MNG) and follicular carcinoma has been reported in the same family (Karges et al, 2005). To date, more then 55 germline gainof-function mutations have been reported, about 14 of them sporadic and the others with familial occurrence (http: www.hgmd.cf.ac.uk/ac/gene.php?gene=TSHR) (Akcurin et al, 2008;Davies et al, 2005;Farid et al, 2000;Führer et al, 1997(b);Holzapfel et al, 1997;Karges et al, 2005;Khoo et al, 1999;Tonacchera et al, 1996;Van Sande et al, 1995). Hyperthyroidism in affected individuals is often resistant to the conventional treatment used in Graves' disease, and either radiotherapy or total thyroidectomy is required.…”
Section: Gain-of-function Mutations In Tshrmentioning
confidence: 99%